2016
DOI: 10.1093/molbev/msw191
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Digestive Enzymes and RNASE1 Provides Insights into Dietary Switch of Cetaceans

Abstract: Although cetaceans (whales, porpoises, and dolphins) have multi-chambered stomachs, feeding habits of modern cetaceans have dramatically changed from herbivorous to carnivorous. However, the genetic basis underlying this dietary switch remains unexplored. Here, we present the first systematic investigation of 10 digestive enzymes genes (i.e., CYP7A1, CTRC, LIPC, LIPF, PNLIP, PGC, PRSS1, SI, SLC5A1, and TMPRSS15) of representative cetaceans, and the evolutionary trajectory of RNASE1 in cetartiodactylans. Positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 60 publications
5
32
0
2
Order By: Relevance
“…A similar phenomenon is known to have occurred in leaf-eating monkeys, where a secondary form of RNase 1 evolved to participate in ruminant-like digestion [31]. Analogously, modern whales and dolphins, which share a common ancestor with cattle, seemingly lost their extra copies of RNase 1 concurrent to switching from a herbivorous to a carnivorous diet [32]. Taken together, extant evidence suggests that cow RNase A—the original so-called “pancreatic ribonuclease”—might be a functional outlier among RNase 1 homologs, with the true physiological role of RNase 1 in other vertebrates still to be unveiled.…”
Section: Introductionmentioning
confidence: 83%
“…A similar phenomenon is known to have occurred in leaf-eating monkeys, where a secondary form of RNase 1 evolved to participate in ruminant-like digestion [31]. Analogously, modern whales and dolphins, which share a common ancestor with cattle, seemingly lost their extra copies of RNase 1 concurrent to switching from a herbivorous to a carnivorous diet [32]. Taken together, extant evidence suggests that cow RNase A—the original so-called “pancreatic ribonuclease”—might be a functional outlier among RNase 1 homologs, with the true physiological role of RNase 1 in other vertebrates still to be unveiled.…”
Section: Introductionmentioning
confidence: 83%
“…Unlike RNase1, which has been extensively studied with gene duplication events observed in many mammals (Zhang et al 2002;Liu et al 2014;Wang et al 2016;Lang et al 2017), RNase6 has been examined in only a few species (Rosenberg & Dyer 1996;Deming et al 1998;Dyer et al 2004;Goo & Cho 2013). We studied 27 species representing the 3 main lineages of rodents and 10 families to investigate the evolutionary mechanism of RNase6.…”
Section: Discussionmentioning
confidence: 99%
“…Novel physiological functions may have evolved in group B and group C, which is reflected by selection pressures, key sites, isoelectric points and positive net charge. Positive selection has been used as one of the key evolutionary forces for the functional divergence of the duplicate genes and the association between positive selection and function divergence has been reported in some members of the RNase A superfamily (Zhang et al 2002;Liu et al 2014;Wang et al 2016;Lang et al 2017). One of the classical examples is the eosinophil-derived neurotoxin (EDN) and eosinophil cationic protein (ECP) of humans (Zhang et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative analysis of cetacean genomes has provided important insights into the genomic determinants of cetacean traits and aquatic specializations (8). Several studies revealed patterns of positive selection in genes with roles in the nervous system, osmoregulation, oxygen transport, blood circulation, protein and lipid digestion, or bone microstructure (9)(10)(11)(12)(13)(14)(15)). An adaptive increase in myoglobin surface charge likely permitted a high concentration of this oxygen transport and storage protein in cetacean muscles (16).…”
Section: Introductionmentioning
confidence: 99%